2015
DOI: 10.1074/jbc.m114.610402
|View full text |Cite
|
Sign up to set email alerts
|

Fe-S Cluster Biogenesis in Isolated Mammalian Mitochondria

Abstract: Background: Fe-S cluster assembly in mitochondria involves generation of an activated form of sulfur called persulfide. Results: A novel experimental system tracks new Fe-S cluster synthesis in isolated mammalian mitochondria. Conclusion: The use of persulfide sulfur and iron for Fe-S cluster biogenesis is tightly coordinated by processes requiring GTP, NADH, and ATP. Significance: These cofactor targets can now be defined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 64 publications
1
13
0
Order By: Relevance
“…The reasons why this occurs and how the PANK2 deficiency is involved are still obscure. Very recent data, obtained on isolated mammalian mitochondria, demonstrated that ISC biosynthesis requires, other than iron and sulphur, also GTP, NADH and ATP ( Pandey et al, 2015 ). A very reliable hypothesis could be that the impairment of the Krebs cycle due to CoA deficiency might result in lower production of GTP and NADH, with the consequent partial iron utilisation in ISC biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons why this occurs and how the PANK2 deficiency is involved are still obscure. Very recent data, obtained on isolated mammalian mitochondria, demonstrated that ISC biosynthesis requires, other than iron and sulphur, also GTP, NADH and ATP ( Pandey et al, 2015 ). A very reliable hypothesis could be that the impairment of the Krebs cycle due to CoA deficiency might result in lower production of GTP and NADH, with the consequent partial iron utilisation in ISC biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…The persulfides, which are also intermediates in the synthesis of particular sulfur biomolecules [30,31], are nowadays being considered candidate species for the transduction of the signals triggered by H 2 S. Not only are these species suggested to be more nucleophilic and acidic than the original thiols, but they also show an electrophilic character that is lacking in the original thiols [32]. In addition, enzymatic pathways for the H 2 S–independent formation of persulfides have been reported [33,34,35,36,37,38,39,40,41,42].…”
Section: Persulfides As Potential Transducers Of H2s Signalingmentioning
confidence: 99%
“…In the last 15 years, increasing efforts have been dedicated to understand the mechanism of iron-sulfur cluster biogenesis because this is an essential machine common to all organisms which increasingly appears to have an important role in human disease. Precious new information was obtained by studies in cellular or animal models, such as yeast, drosophila (Kondapalli et al, 2008 ) and mice (Pandey et al, 2015 ). In vitro studies, which work with a well-defined number of highly purified components, have nevertheless remained essential to clarify the role of each of the players and understand the chemistry which drives cluster formation.…”
Section: Discussionmentioning
confidence: 99%